Studies on some new pyrazolo [3,4-c] pyridine derivatives as antimicrobial egents - (:unkn) unknown (My University, 2009)
İlaçlara karşı direnç kazanmış patojen bakterilerin ve fungusların klinik önemindeki artış, yeni mikrobiyolojik araştırmalara ve yeni antimikrobiyal ilaçların geliştirilmesi çalışmalarına neden olmuştur. Bu amaçla, 2-kloro-N-(benzhidril)asetamid (la) / 2-kloro-N-(l-feniletil) asetamid (lb) ve pirazolo[3,4-cjpiridin türevleri (2) reaksiyona sokularak bir seri N-[(benzhidril)/(l-feniletil)]-2-pirazolo[3,4-c]piridin-l-il asetamid türevi (3a-m) sentezlenmiştir. Bileşiklerin kimyasal yapıları elemental analiz, İR, H-NMR, FAB+-MS verileri ile aydınlatılmıştır. Bunların antimikrobiyal aktiviteleri E. coli (ATCC 11229), S. aureus (ATCC 6538), B. cereus (ATCC 11778), P. mirabilis (ATCC 14153), P. aeruginosa (ATCC 1539), K. pneumoniae (ATCC 4352), C. albicans (ATCC 26555), C. guilliermondii (KUEN 998), C pseudotropicalis (kefyr) (KUEN 1014), and C. krusei (ATCC 6258) suşlarına karşı araştırılmıştır. B. cereus and S. aureus suşlarına karşı bileşiklerin bazısı zayıf derecede aktivite sonuçları gösterirken, aynı bileşikler Candida türlerine karşı herhangi bir aktivite göstermemiştir.

The increasing clinical importance of drug-resistant bacterial and fungal pathogens has lent additional urgency to microbiological research and novel antimicrobial compounds development. For this aim, a series of N-[(Benzhydryl) / (l-phenylethyl)j-2-pyrazolo[3,4-c]pyridin-l-yl acetamide derivatives (3a-m) were synthesized by reacting 2-chloro-N-(benzhydryl)acetamide (la) / 2-chloro-N-(1-phenylethyl)acetamide (lb) andpyrazolo[3,4-c]pyridine derivatives (2). The chemical structures of the compounds were elucidated by elemental analyses, IR, !H-NMR, FAB+-MS spectral data. Their antimicrobial activities against E. coli (ATCC 11229), S. aureus (ATCC 6538), B. cereus (ATCC 11778), P. mirabilis (ATCC 14153), P. aeruginosa (ATCC 1539), K. pneumoniae (ATCC 4352), C. albicans (ATCC 26555), C. guilliermondii (KUEN 998), C. pseudotropicalis (kefyr) (KUEN 1014), and C krusei (ATCC 6258) were investigated. The results showed that some of the compounds have slight activity against B. cereus and S. aureus. Whereas, the same compounds did not show any significant antifungal activity against Candida species.
Antimikrobiyal ajan olarak bazı pirazolo [3,4-c] piridin türevleri üzerine çalışmalar
Keywords: Farmakoloji ve Eczacılık